Narrative review: Ultra-processed foods and the risk of metabolic syndrome - Prananingrum Kinasih; Miftahul Jannah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Ultra-processed foods generally contain high levels of energy, sugar, sodium, and saturated fat, and low levels of fiber and micronutrients. Excessive consumption of ultra-processed foods can potentially trigger metabolic dysfunction via inflammatory pathways, insulin resistance, and lipid homeostasis disorders. This study aimed to review the scientific evidence regarding the relationship between ultra-processed food consumption and the risk of metabolic syndrome. This narrative literature review was conducted using a systematic search of the PubMed and ScienceDirect databases (2020–2025). The inclusion criteria were observational studies on related topics, articles in English, and full texts, while the exclusion criteria were studies on animals/cell cultures and non-full-text articles. The results of this study showed a consistent relationship between UPF consumption and an increased risk of metabolic syndrome. Individuals in the highest quartile of UPF consumption were 3.27 times more likely to develop metabolic syndrome (OR=3.27; 95% CI: 2.76–3.89; p<0.001). Additionally, high UPF consumption was associated with increased weight, BMI, waist circumference, blood pressure, fasting blood glucose, HbA1c levels, and triglyceride levels. In conclusion, high UPF consumption consistently increases the risk of metabolic syndrome; therefore, limiting UPF and improving the diet may be a preventive strategy.